Nutritional profile of elderly female residing in a geriatric institution - Dantas Moreira, Johara Patrícia (2012)
Objective: To assess the nutritional profile of elderly women residing in a geriatric institution in Fortaleza-CE, Brazil. Methods: The elderly residing for more than 3 months in the institution were evaluated by measurement of weight, height, arm circumference (AC) and calf circumference (CC). Their Body Mass Index (BMI) was calculated and the Nutritional Mini Evaluation (NME) was also applied to the participants. Results: The study involved 28 elderly women, among which 22 (78,6%) did not show risk of malnutrition, according to the NME, those being evaluated through BMI, AC and CC. The BMI calculated for those participants revealed that 12 (54,5%) were eutrophic, 8 (36,4%) were overweight and 2 (9,1%) were underweight. According to the AC, 3 (13.6%) were overweight, 9 (40.9%) eutrophic and 10 (45.4%) underweight and, according to CC, 5 (22.7%) were malnourished and 17 (77.3%) with adequate deposit of muscle mass. To 6 (21,4%) of the elderly that scored equal lower than 11, the entire roll of items proposed in NME was, therefore, applied. Among those, 4 (66,7%) presented risk of malnutrition and 2 (33,3%) were malnourished. Conclusion: The results show that elderly women residing in this institution were found eutrophic in most of the evaluated parameters.